(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
Conceived as a stage of a research on the medieval Seggi in Southern Italy, the essay explores the forms by which the urban space of Naples is described and controlled from the 10th to the 14th century, with particular regard to plateae and regiones, and to the territorial micro-societies called ‘tocchi’. The aim is to reopen, also thanks to unpublished sources, the question of the presence of the tocchi from the mid 12th to the 14th century, investigating a practice of urban space control, by which groups of nobiliores or boni homines belonging to a regio or a toccum granted the absolutio to legally act to certain subjects. This practice identifies in the rootedness and urban space-control made by eminent families of nobiliores a criterion of social distinction in a context of strong urbanisation, and is analysed for the first time in relation to the social context of the act and its formalisation in the chartae of the curiales.